Expanding the Scope of Pnictogen‐Assisted Cyclophane Self‐Assembly. Issue 26 (31st March 2022) - Shear, Trevor A.; Mayhugh, Jacob T.; Zocchi, Luca J.; Demachkie, Isabella S.; Trubenstein, Henry J.; Zakharov, Lev N.; Johnson, Darren W.
Abstract: Cyclophanes are a fundamentally interesting class of compounds that host a wide range of unique and emergent properties. However, synthesis of complex and/or functionalized cyclophanes can often suffer from harsh reaction conditions, long reaction times, and sometimes low yields using stepwise methods. We have previously reported an efficient, high‐yielding, metalloid‐directed self‐assembly method to prepare disulfide, thioether, and hydrocarbon cyclophanes and cages that feature mercaptomethyl‐arenes as starting materials. Herein, we report the synthesis of 21 new disulfide and thioether assemblies that expand this high yielding self‐assembly method to a wide breadth of macrocycles and cages with diverse structures. Remarkably, the high‐yielding, efficient syntheses still proceed under dynamic covalent control using electron‐deficient, heteroaryl, cycloalkyl, spiro, and even short alkenyl/alkynyl substrates. Abstract : Using metalloid‐assisted self‐assembly, substrate compatibility was explored. 21 new disulfide and thioether macrocycles were synthesized that incorporated a wide breadth of structural and electronic properties.